Improving Postpartum Attendance among Women with Gestational Diabetes Using the Medical Home Model of Care - Soffer, Marti D.; Rekawek, Patricia; Pan, Stephanie; Overbey, Jessica; Stone, Joanne (American Journal of Perinatology, 2021)
Objective Poor attendance at the 6-week postpartum (PP) visit has been well reported. Attendance at this visit is crucial to identify women who have persistent diabetes mellitus (DM) following pregnancies affected by gestational DM (GDM). The medical home model has eliminated barriers to care in various other settings. This study sought to improve PP attendance among women with GDM by jointly scheduling PP visits and the 2-month well infant visits.Study Design All patients with a diagnosis of GDM who received care at a New York City–based publicly insured hospital clinic and delivered between October 2017 and June 2019 were eligible. Data were obtained via chart review. The primary outcome was attendance at the PP visit compared with previously published historical controls. Secondary outcomes were rates of PP glucose screening and well infant attendance.Results Of the 74 patients enrolled, 41.9% were Hispanic and 17.6% were Black, mean age was 31.6 years, and 58.1% delivered vaginally. Attendance at the 6-week PP visit was 68.9%, and attendance at the infant visit was 55.1%. PP glucose testing was ordered for 76.5% of attendees at the PP visit, and of those ordered, 43.6% of attendees completed testing. All patients had joint visits requested, though only 70.3% of visits were scheduled jointly. Among those who were jointly scheduled, 71.2% of women attended, 57.7% of infants attended, and 7.7% of pairs attended on the same day. The PP visit attendance rate was not significantly different than the prior attendance rate (p = 0.84).Conclusion This study was unable to improve PP visit attendance among women with GDM by jointly scheduling the 6-week PP visit and the 2-month well-infant visit. Future research could be directed toward a shared space where both women and children can be seen to attempt to increase PP visit attendance and monitoring for women with GDM.Key Points
Keywords: gestational diabetes; medical home; postpartum; postpartum attendance